UJI EFEK ANTIPIRETIK INFUSA DAUN SESEWANUA (Clerodendron squamatum Vahl.) TERHADAP KELINCI JANTAN YANG DIINDUKSI VAKSIN DTP HB - Moot, Clementia Luigy; Bodhi, Widdhi; Mongi, Jeane (PHARMACON, 2013)
ABSTRACT Sesewanua leaves (Clerodendron squamatum Vahl.) empirically used for an alternavite fever treatment. The aims of this study was to investigate infuse of Sesewanua leaves had antipyretic effectts for rabbits induced by vaccine DTP HB. This assay uses 15 rabbits grouped into 5 groups, the negative control (destilled water), the treatment (infuse of Sesewanua leaves 20%, 40% and 80%) and a positive (parasetamol). Rabbits induced pyrexia with vaccine DTP HB doses 0,25ml/KgBB by intramuscular route. Rabbit’s rectal temperature was measured every 1 hour until 4 hours after the oral administration. The decrease of rabbit’s rectal temperatur were analyzed by one way ANOVA and LSD test (α = 0,05%). The result showed that infuse of Sesewanua in concentrates 20%, 40% and 80% had antipyretics effect for rabbits induced by vaccine DTP HB. Keywords : Antipyretics effect test, Clerodendron squamatum Vahl., Vaccine DTP HB, rabbits